Effect of Melatonin on Passive, Ex-Vivo Biomechanical Behavior of Lamb Esophagus - Garcia-Herrera, C; Rivera-Mancilla, E; Godoy-Guzman, C; Bezmalinovic-Colleoni, A (Nature Research, 2025)
One of the purposes of tissue engineering is to offer therapeutic alternatives to treat various esophagus-related diseases. To develop viable esophageal replacements that are both mechanically and biologically compatible and to assess the impact of pharmacological treatments on esophageal tissue at the macro- and micro-structural levels, it is crucial to understand the biomechanical properties of the esophagus. In this study, we analyzed esophageal tissue samples from nine newborn lambs. Subjects were randomly separated into a control group (n = 5) and a melatonin-treated group (n = 4). The passive mechanical response of the esophagus was studied by performing in-vitro uniaxial tensile tests along longitudinal and circumferential directions. Samples were classified into three types: internal tissue (mucosa and submucosa layers), external tissue (external muscular layer), and integrated tissue (comprising all layers). Uniaxial stress versus stretch curves of each classification were used to determine mechanical properties that were statistically analyzed. Moreover, average experimental results were used to calibrate an anisotropic hyperelastic model. Stress-stretch curves from uniaxial tests showed a highly anisotropic behavior, with a higher stiffness along the longitudinal direction and internal tissue exhibiting the highest stiffness. To contrast the results obtained from mechanical testing, histological analysis of esophagus samples was carried out. Microstructural components were quantified and morphological measurements of the main zones were performed. No significant differences were found at the macro- and microstructural levels of the tissue, indicating that the supply of low doses of melatonin does not alter the biomechanical properties of the esophagus. © The Author(s) 2025.